KONSEP DAN IMPLEMENTASI PEMBANGUNAN PERTANIAN BERKELANJUTAN DI INDONESIA (Forum Penelitian Agro Ekonomi, 2024)
Sustainable development including that of agriculture is all of the countries’ commitment to implement. Previous development implementation focused on economic progress resulting in environmental degradation and social problems. Sustainable development approach is basically development activities integrating economic, social, and environmental aspects. However, this concept is not fully implemented by all of the countries as depicted in the agreement. It is indicated by many problems related with environmental degradation and natural resources deprivation. Implementation of sustainable agricultural development deals with some constraints especially in developing countries including in Indonesia. One of the main constraints in Indonesia is interest conflict among sectors leading to separated implementation.  Sustainable development concept is a multi-dimensional approach implemented through integrated program among sectors both at central and regional levels.